2016
DOI: 10.1074/jbc.m116.714733
|View full text |Cite
|
Sign up to set email alerts
|

Cross-talk between Dopachrome Tautomerase and Caveolin-1 Is Melanoma Cell Phenotype-specific and Potentially Involved in Tumor Progression

Abstract: L-Dopachrome tautomerase (L-DCT), also called tyrosinaserelated protein-2 (TRP-2), is a melanoma antigen overexpressed in most chemo-/radiotherapeutic stress-resistant tumor clones, and caveolin-1 (CAV1) is a main regulator of numerous signaling processes. A structural and functional relationship between DCT and CAV1 is first presented here in two human amelanotic melanoma cell lines, derived from vertical growth phase (MelJuSo) and metastatic (SKMel28) melanomas. DCT co-localizes at the plasma membrane with C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 73 publications
0
6
0
Order By: Relevance
“…6 b], NanoString™ analysis revealed additional, heretofore unrecognized expression changes [downregulation: TGFBI (5.9-fold), CTSK (4.7-fold), ANGPTL4 (4.7-fold), FLT1 (3.8-fold), CAV1 (3.2-fold), MGP (3.1-fold), KDR (3.1-fold), TLR4 (3.0-fold), NR4A1 (2.9-fold), THBS1 (2.8-fold); upregulation: SERPINF1 ( PEDF ; 4.7-fold); ( Fig. 6 b)], all with established roles in melanoma invasion and metastasis, and therefore potentially involved in attenuation of EMT in response to GLO1 deletion [ [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…6 b], NanoString™ analysis revealed additional, heretofore unrecognized expression changes [downregulation: TGFBI (5.9-fold), CTSK (4.7-fold), ANGPTL4 (4.7-fold), FLT1 (3.8-fold), CAV1 (3.2-fold), MGP (3.1-fold), KDR (3.1-fold), TLR4 (3.0-fold), NR4A1 (2.9-fold), THBS1 (2.8-fold); upregulation: SERPINF1 ( PEDF ; 4.7-fold); ( Fig. 6 b)], all with established roles in melanoma invasion and metastasis, and therefore potentially involved in attenuation of EMT in response to GLO1 deletion [ [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…6 ) [ 26 ]. Strikingly, a large number of genes shown here for the first time to be responsive to GLO1 expression status (including TXNIP , ANGPTL4 , CAV1 , CTSK , FLT1 , KDR , NRP1 , NR4A1 , SERPINF1 , TGFBI , THSB1 , TLR4 ) have previously been associated with EMT in melanomagenesis [ [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , 65 ]. For example, concerted upregulation of VEGF-receptor expression ( FLT1 , KDR , NRP1 ) together with trombospondin-1 ( THSB1 ) has been associated with melanoma progression [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is an example of cross-talk in melanoma molecularity. Our group has also identified such a reciprocal modulating mechanism in melanoma cells between caveolin-1, a major regulator of signaling platforms and dopachrometautomerase, a melanoma antigen with multiple functions, including melanoma resistance to therapeutical and environmental stress [ 178 ]. Importantly, this IL-8 mediated pathway has not been described, so far, to our knowledge, in other neoplasms.…”
Section: Interleukin 8—a Major Key-player In CM Pathogenesismentioning
confidence: 99%
“…Using multienzyme digestion and different fragmentation techniques [57] available on the hybrid ion trap-Orbitrap platform, Chiritoiu et al reported the occupancy of all N-glycosylation sites of tyrosinase in a melanoma cell line [58], an enzyme shown to be correlated with patient clinical evolution in melanoma [59,60]. Moreover, recent evidence suggests that even other members of the tyrosinaserelated protein family could be also linked to melanoma progression [61,62].…”
Section: Melanoma Biomarkersmentioning
confidence: 99%